Effect of Carbonization Pressure on CO2 Sequestration and Rheological Properties of Coal Gangue-Based Backfilling Slurry - Lei Zhu; Zhicheng Liu; Qiang Guo; Binbin Huo; Nan Zhou; Yuejin Zhou; Meng Li; Wenzhe Gu (Applied Sciences)
The wet carbonation of coal gangue-based backfilling slurry (CGBS) is considered to be an effective method for the resource utilization of coal gangue solid waste and CO2 sequestration, but CO2 sequestration has a negative impact on the rheological properties of CGBS. This investigation explores the effect of carbonization pressure on the rheological properties and CO2 sequestration properties of CGBS by using a carbonization reactor, a rheometer, X-ray diffraction, a nitrogen adsorption–desorption instrument, a scanning electron microscope and other testing methods. The results show that increasing the carbonization pressure can increase the CO2 sequestration capacity of CGBS, and the carbonization products produced make the pores of CGBS smaller and the structure more compact; however, increasing the carbonization pressure will reduce the rheological properties of the slurry, and the optimal carbonization pressure is 0.7 MPa. At this time, the yield stress, plastic viscosity and hysteresis loop area of CGBS are 171.66 Pa, 0.0998 Pa·s and 1376 Pa/s, respectively. However, when the carbonization pressure is further increased, the CO2 sequestration capacity tends to remain unchanged. This is mainly because the carbonization pressure causes the carbonization reaction to intensify, forming a calcified layer on the particle surface, which hinders the penetration of CO2 into the particles. This study is of great significance for improving the utilization rate of gangue solid waste and CO2 sequestration.